2020
DOI: 10.3390/ijms21239250
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Gentamicin or Vancomycin Containing Bone Graft Substitute in the Prevention of Orthopedic Implant-Related Infections

Abstract: Antibiotic-loaded bone graft substitutes are attractive clinical options and have been used for years either for prophylaxis or therapy for periprosthetic and fracture-related infections. Calcium sulfate and hydroxyapatite can be combined in an injectable and moldable bone graft substitute that provides dead space management with local release of high concentrations of antibiotics in a one-stage approach. With the aim to test preventive strategies against bone infections, a commercial hydroxyapatite/calcium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Various biodegradable carriers have been designed for antibiotics, such as CERA-MENT™, which is composed of 40% hydroxyapatite and 60% calcium sulfate. CERA-MENT™ is involved in the bone healing process in combination with vancomycin and gentamicin [144]. Gimeno et al (2018) demonstrated a high effectivity of cefazolin-loaded orthopedic implants [145].…”
Section: Ssi Associated With Orthopedic Implantsmentioning
confidence: 99%
“…Various biodegradable carriers have been designed for antibiotics, such as CERA-MENT™, which is composed of 40% hydroxyapatite and 60% calcium sulfate. CERA-MENT™ is involved in the bone healing process in combination with vancomycin and gentamicin [144]. Gimeno et al (2018) demonstrated a high effectivity of cefazolin-loaded orthopedic implants [145].…”
Section: Ssi Associated With Orthopedic Implantsmentioning
confidence: 99%
“…The current study demonstrated that the AMPs melimine and Mel4 at sub-MICs did not induce resistance in S. aureus ATCC 25923. We and others [28][29][30][31] have tested several broad-spectrum antibiotics such as gentamicin (data not shown in the current study) and ciprofloxacin to determine whether strains such…”
Section: Discussionmentioning
confidence: 92%
“…The current study demonstrated that the AMPs melimine and Mel4 at sub-MICs did not induce resistance in S. aureus ATCC 25923. We and others [28][29][30][31] have tested several broad-spectrum antibiotics such as gentamicin (data not shown in the current study) and ciprofloxacin to determine whether strains such as S. aureus ATCC 6538, ATCC 25923, 31 and 38 can develop resistance to gentamycin and ciprofloxacin. Resistance to gentamicin or ciprofloxacin was not induced in any strain except S. aureus ATCC 25923 which developed resistance against ciprofloxacin.…”
Section: Discussionmentioning
confidence: 93%
“…The infection rates under use of bone substitute materials are reported to be up to 12% [ 3 ]. The bacterial spectrum in IRI consists with mainly staphylococci followed by streptococci, enterococci, Gram-negative rods and anaerobs [ 59 ]. This is in line with the findings in periprosthetic joint infection (PJI).…”
Section: Antibiotic Eluting Bone Substituentsmentioning
confidence: 99%